1999
DOI: 10.1108/02652329910258934
|View full text |Cite
|
Sign up to set email alerts
|

Provision of electronic banking in the UK and the Republic of Ireland

Abstract: Electronic or online banking is the newest delivery channel to be offered by the retail banks in many developed countries and there is wide agreement that this channel will have a significant impact on the market. Aims to quantify the current provision of electronic services by major retail banking organisations in the UK and the Republic of Ireland. Additional insight into the banks‘ adoption of this new channel is gained by exploring two areas important in the analysis of new offerings, that is: an organisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
243
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(277 citation statements)
references
References 34 publications
3
243
1
2
Order By: Relevance
“…Roboff and Charles (1998) note that although customers' confidence in their bank is strong, yet their confidence in the technology is weak (Howcroft, et al, 2002). According to Daniel (1999), security concerns arise from the use of an open public network. Therefore, this study considers security concerns as an important factor in adoption of mobile banking.…”
Section: Literature Review and Conceptual Background Risky Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Roboff and Charles (1998) note that although customers' confidence in their bank is strong, yet their confidence in the technology is weak (Howcroft, et al, 2002). According to Daniel (1999), security concerns arise from the use of an open public network. Therefore, this study considers security concerns as an important factor in adoption of mobile banking.…”
Section: Literature Review and Conceptual Background Risky Technologiesmentioning
confidence: 99%
“…This research follows their definition for mobile banking adoption. As mobile banking is a highly personalized service as well as a global communication medium, it is exposed to many security vulnerabilities (Daniel, 1999). According to Daniel (1999), security concerns arise from the use of an open public network.…”
Section: Figure 1 Research Modelmentioning
confidence: 99%
“…22 One consequence of the Internet is the growing virtualisation movement. 23,22 -25 By ' virtualisation ' , we understand the removal of all constraints of time, place and method, enabled by the convergence of computing, telecommunications and visual media.…”
Section: Nicts and Internet Use In Bankingmentioning
confidence: 99%
“…A lot of surveys showed that it is possible to reduce banking network costs in this way. Daniel (1999) is probably one of the firsts to show banks can improve their efficiency through technology adoption. The author showed that corporate vision of the future in which the environment becomes more competitive can propel it to use online services.…”
Section: Introductionmentioning
confidence: 99%